Advocacy Through Education. (August 2017) - Perry, Cheryl; Emory, Jan
Nurses are one of the largest groups of policy stakeholders in the health-care workforce, yet their influence on policy is not necessarily commensurate with their numbers. Since 2011, grassroots action coalitions have emerged to advance the profession's impact on health-care policy. In one state, a partnership among professional nursing organizations, policy stakeholders, and academics resulted in educational presentations focused on political advocacy knowledge and skills. The goal of this project was to bring awareness to nurses and nursing students about their potential contributions to the political and advocacy processes that shape health policy. The purpose of this study was to determine the effectiveness of focused educational presentations in correcting misconceptions, increasing awareness, and providing clarification of the roles of advanced practice registered nurses, and identifying related policy implications. This quasi-experiment used a retrospective pre–post intervention self-evaluation tool administered immediately following an educational presentation. The sample ( N  = 137) consisted of baccalaureate nursing students and licensed nurses. The results showed ( p  < .001) that education could have a significant improvement in political advocacy participation.